2019
DOI: 10.3892/etm.2019.8222
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of cathepsin S with coronary stenosis degree, carotid thickness, blood pressure, glucose and lipid metabolism and vascular endothelial function in atherosclerosis

Abstract: Correlation of cathepsin S with coronary stenosis degree, carotid thickness, blood pressure, glucose and lipid metabolism, and vascular endothelial function in patients with atherosclerosis was investigated. Data from 120 patients with increased cathepsin S levels (increased group) and 120 subjects with normal cathepsin S levels (normal group) were retrospectively analyzed. The serum cathepsin S level and Gensini score were compared between the healthy subjects and patients with coronary atherosclerotic heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Indeed, cardiac disease has been described in MPS III patients as well as in patients affected by the other MPS subtypes [178,179]. Multiple evidence demonstrated the involvement of CTSs in many cardiovascular diseases, including atherosclerosis, cardiac hypertrophy, cardiomyopathy, myocardial infarction, and hypertension, some of which are common clinical manifestations in MPSs [8,10,[17][18][19]36,56,61,66,76,80,81]. In particular, CTSB results in being up-regulated in cardiomyocytes in response to hypertrophic stimuli both in vivo and in vitro [180].…”
Section: Cathepsin Involvement In the Pathophysiology Of Mucopolysaccmentioning
confidence: 99%
“…Indeed, cardiac disease has been described in MPS III patients as well as in patients affected by the other MPS subtypes [178,179]. Multiple evidence demonstrated the involvement of CTSs in many cardiovascular diseases, including atherosclerosis, cardiac hypertrophy, cardiomyopathy, myocardial infarction, and hypertension, some of which are common clinical manifestations in MPSs [8,10,[17][18][19]36,56,61,66,76,80,81]. In particular, CTSB results in being up-regulated in cardiomyocytes in response to hypertrophic stimuli both in vivo and in vitro [180].…”
Section: Cathepsin Involvement In the Pathophysiology Of Mucopolysaccmentioning
confidence: 99%
“…In a clinical study performed on 120 patients with high serum cathepsin S levels vs. age and sex-matched controls, the incidence of coronary artery disease and hypertension was significantly higher, and the intima-media thickness was also increased. Serum cathepsin S levels correlated strongly with the Gensini score, and patients with multi-vessel coronary artery involvement had higher Cat S than those with double-, or only single-vessel involvement [29]. Circulating forms of pro-cathepsin S, and active cathepsin S along with Cys C were higher in the plasma of abdominal aneurysm patients, and the latter two proved to be independent risk factors in multivariate logistic regression models [30].…”
Section: Discussionmentioning
confidence: 89%
“…In APCs, cathepsin S gene knockout or inhibition by small molecule compounds reduces the degradation of CD74 and prevents the binding of MHC II to antigen peptides, thus reducing antigen presentation to CD4 + T cells ( 96 ). Studies have found that the increase of serum cathepsin S level was related to the aggravation of coronary artery stenosis, carotid artery thickening, blood pressure increase, and abnormal vascular endothelial function ( 97 ). However, it is not related to the increased risk of cardiovascular events in patients with stable coronary heart disease ( 98 ).…”
Section: Treatment Strategies That Target Cd74mentioning
confidence: 99%